Immature Gastroesophageal Teratoma: Second Case Report and Literature Review - Yasir S. Jamal; Husain I. Sandugji; Mazen O. Kurdi; Hayat Z. Kamfar; Rana Y. Bokhary; Abdel-Rahman R. Abdel-Halim; Loai S. Jamal (Journal of King Abdulaziz University: Medical Sciences, 2023)
Gastric and gastroesophageal teratoma are rare tumors that involve the stomach and gastroesophageal zone, both are of the same pathological nature. In reviewing literature, nearly 110 cases were reported, but the teratoma that involved the gastroesophageal area is extremely rare as only one case of mature gastroesophageal teratoma has been reported previously. Presented is the second case of gastroesophageal teratoma; a case of 18-days-old male patient with large immature gastroesophageal teratoma which was recognized as abdominal mass on antenatal ultrasound, but patient presented five days after noticing the abdominal mass by his mother. Discussion with the relevant technical considerations in the management of the teratoma originating from or involving the gastro-esophageal junction was considered.